Macrofauna from the sandy shore of the Johnny Cay Regional Natural Park, San Andrés and Providencia, biosphere reserve, Colombian Caribbean region - Daniela Y. Gaurisas; Eliana Barrios-Vásquez; Catalina Arteaga-Flórez; Maria A. Mutis-Martinezguerra; Bibian Martínez-Campos (Ocean and Coastal Research)
Despite their great importance, the sandy shores have not received the attention deserved. In Colombia they have been approached mainly from physical and geological standpoints, with few studies on the associated biodiversity, as is the case of the Johnny Cay Regional Natural Park in the Colombian Caribbean Region. To have a future frame of reference to evaluate and monitor the environmental impact on the sandy coast of Johnny Cay, the macrofaunal community of this ecosystem was characterized. Two stations were established, where three sediment samples were taken per beach zone (infralittoral, mesolittoral, and supralittoral), using a 16 cm diameter core, for a total of nine samples per station. The samples were sieved through a 500 µm mesh and processed in a laboratory. The macrofaunal community of Johnny Cay was represented by 1628 organisms, belonging to 20 families of the phyla Annelida, Nematoda, Mollusca, and Arthropoda (subphylum Crustacea). Annelids were the dominant group, representing 98% of total abundance, with two new family reports (Naididae and Enchytraeidae) for the Colombian Caribbean sandy beaches. The station EST_549 presented 67% of the macrofauna; this station is characterized by its hydro-dynamism, with a change of material due to the division in the opposite direction of the waves. Substrate samples were also taken in each beach zone for sedimentological analysis of grain size, carbonate content, organic matter content, and mineralogy; these variables were correlated with the community structure, obtaining a better correlation between the medium and coarse sands, and the width of the beach zone with the biological component. This work presents the baseline for the macrofaunal community of Johnny Cay sandy shore and sets the initial steps for its preservation and conservation.